Peningkatan Literasi Anak Gereja Melalui Pojok Baca Dan Cerita Pendek Di Gereja HKBP Parsaoran Nauli Resort Sola Fide - Dame Ifa Sihombing; Kikin Simaremare; Claudya Gita Br Pa; Sartika Maria Siregar; Indah Lestari Hasugian (Yayasan Kajian Riset Dan Pengembangan Radisi, 2026)
Developing literacy skills in children is crucial and needs to be instilled from an early age, as it plays a key role in developing reading skills, understanding information, and fostering learning habits. The church, as a religious institution, not only performs a religious function but also plays a role in supporting the education and development of children. This community service activity aims to improve the literacy of Sunday school children through a reading corner program and short story telling activities at the HKBP Parsaoran Nauli Resort Sola Fide Church. The method used in this activity is an educational mentoring approach implemented through several stages: preparation, implementation, and evaluation. During the preparation stage, observations were made on children's literacy conditions and coordination with church administrators and Sunday school teachers. The implementation stage involved providing a reading corner in the form of a creative wall magazine containing illustrated stories and Bible stories, as well as storytelling activities using interesting props to facilitate children's understanding of the story. Furthermore, the evaluation stage was conducted by observing children's interest, participation, and responses during the activity. The results of the activity showed that providing interactive reading facilities and storytelling activities increased children's interest in reading and helped them understand the story's content and convey the message they received. This program also provided a fun learning experience, making children more active in the learning process. Thus, reading corner and short story activities can be an effective effort to foster a culture of literacy while instilling moral